Improving the Ability to Analyze Kinematics Problems Through the Matriculation Program - Sopacua, Venty; Sopacua, Fryan (Pascasarjana, Mataram University, 2024)
This study aims to describe the improvement of the ability to analyze kinematics problems through the matriculation program. The subjects of this study were 22 New Students of the 2022 Class of Physics Education Study Program, Pattimura University, Ambon. This study uses quantitative and qualitative descriptive research types. The trial design uses a one group pretest–posttest design. The instrument in this study is the Test Instrument, in this case to measure the improvement of the ability to analyze kinematics problems before and after matriculation. Data analysis in this study was carried out using quantitative descriptive analysis to describe the data as it is in the form of percentages and explain data or events with explanatory sentences qualitatively. The data analysis technique used is qualitative descriptive analysis including: kinematics problem analysis test results. The results of the study showed that 90.9% experienced an increase in their ability to analyze kinematics problems in the medium - high category, and 9.1% in the low category did not experience an increase in their ability to analyze kinematics problems, so it can be concluded that marticulation can improve the ability to analyze kinematics problems of physics education students in the Class of 2022